(untitled) (Revista de Ciências Agroveterinárias, 2023)
Canola faces difficulties in its cultivation, such as the occurrence of water scarcity periods. An alternative to mitigate these adversities is the application of plant growth regulators. Therefore, the objective of this work was to evaluate the application of salicylic acid in the initial development of the canola crop subjected to water deficit. The experiment was carried out in a greenhouse, in a randomized block design in a 5x2 factorial scheme, consisting of five doses of salicylic acid (0; 0.5; 1.0; 1.5 and 2.0 mM L-1) and two water regimes, with and without water deficit (25% and 80% of pot capacity), with four replications. The variables analyzed were visual injuries, plant height, chlorophyll content and shoot dry mass. The application of different doses of salicylic acid did not present significant differences in relation to the non-application, for the analyzed variables. The water deficit resulted in a higher percentage of injuries, lower height and dry mass of plants, indicating the occurrence of stress to the crop. The application of salicylic acid did not attenuate the effects of water deficit, as well as it did not demonstrate beneficial effects on plant development.